HEMOLYTIC UREMIC SYNDROME ASSOCIATED WITH STREPTOCOCCUS PNEUMONIAE IN PEDIATRICS: A CASE SERIES - Oscar Javier León Guerra; Ricardo Saul Galeano Rodríguez; William Javier Morales Camacho; Jessica Estefanía Plata Ortiz; María Alejandra Morales Camacho (Sociedade de Pediatria de São Paulo, 2019)
ABSTRACT Objective: To describe a case series of four (4) patients with hemolytic uremic syndrome due to Streptococcus pneumoniae in a level four complexity institution in the city of Bogotá, D.C., Colombia. Cases description: We describe cases of four patients who presented respiratory symptoms and fever. All four patients were in regular conditions on hospital admission, after which they required intensive care and ventilatory support. Upon admission, three cases showed evidence of pleuropulmonary complication. Penicillin-sensitive Streptococcus pneumoniae was isolated in all cases. All patients presented anemia, severe thrombocytopenia, schistocytes on peripheral blood smear, and hyperazotemia. They required blood transfusion and renal replacement therapy during their hospitalization. The patients were diagnosed with hemolytic uremic syndrome due to S. pneumoniae. Three of the four patients had a progressive recovery of the renal function and were discharged after an average of 36 days of hospital stay. The remaining patient had two amputations in the extremities due to thrombotic vascular complications and was discharged after 99 days of hospital stay, requiring hemodialysis every other day. Comments: Hemolytic uremic syndrome due to Streptococcus pneumoniae is a rare but severe complication of invasive pneumococcal disease. Complicated pneumonia is the main condition associated with this entity. It is noteworthy the short period in which these cases were presented, considering the low annual incidence of the disease.